2013
DOI: 10.1136/annrheumdis-2012-202742
|View full text |Cite
|
Sign up to set email alerts
|

New insight on the Xq28 association with systemic sclerosis

Abstract: Objective To evaluate whether the systemic sclerosis (SSc)-associated IRAK1 non-synonymous single-nucleotide polymorphism rs1059702 is responsible for the Xq28 association with SSc or whether there are other independent signals in the nearby methyl-CpG-binding protein 2 gene (MECP2). Methods We analysed a total of 3065 women with SSc and 2630 unaffected controls from five independent Caucasian cohorts. Four tag single-nucleotide polymorphisms of MECP2 (rs3027935, rs17435, rs5987201 and rs5945175) and the IRA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 43 publications
2
39
0
Order By: Relevance
“…Three SNPs of IRAK1 have been found to be related to ADs risk: rs3027898 for RA [15,22], rs1059702 for SSc [23,24] and rs1059703 for SLE [14,25]. However, the results remain in conflict.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three SNPs of IRAK1 have been found to be related to ADs risk: rs3027898 for RA [15,22], rs1059702 for SSc [23,24] and rs1059703 for SLE [14,25]. However, the results remain in conflict.…”
Section: Discussionmentioning
confidence: 99%
“…Four races were included: Caucasian, Asian, African, and Latin-American. Four studies were not in HWE in control groups [14,15,23,24]. …”
Section: Study Characteristicsmentioning
confidence: 90%
“…However, evidence suggests that MeCP2 is not only related to Rett syndrome and MeCP2 duplication syndrome, but may also contribute to primary immunologic disorders, such as systemic lupus erythematosus (SLE) (Kaufman et al, 2013;Koelsch et al, 2013;Sawalha et al, 2008;Webb et al, 2009), primary Sjogren's syndrome (Cobb et al, 2010), systemic sclerosis (Carmona et al, 2013), and rheumatoid arthritis (Han et al, 2013).…”
Section: Mecp2 In Adaptive Immunitymentioning
confidence: 99%
“…However, studies using mice that specifically overexpress only MeCP2, and not IRAK1, have demonstrated that MeCP2 significantly influences immune function on its own (Koelsch et al, 2013;Yang et al, 2012 (Koelsch et al, 2013;Yang et al, 2012), but also MeCP2 loss-of-function / Rett syndrome (Cronk et al, 2015a;Cronk et al, 2015b;Derecki et al, 2012;Horiuchi et al, 2016;Jiang et al, 2014;Jin et al, 2015;Li et al, 2014;Maezawa and Jin, 2010;O'Driscoll et al, 2013b;O'Driscoll et al, 2015), and potentially even other immunologic disorders outside of either Rett or MeCP2 duplication (Carmona et al, 2013;Cobb et al, 2010;Han et al, 2013;Kaufman et al, 2013;Koelsch et al, 2013;Sawalha et al, 2008;Webb et al, 2009). …”
Section: Figures and Tablesmentioning
confidence: 99%
See 1 more Smart Citation